COMMUNITY EMPOWERMENT IN PREVENTING DENGUE FEVER FEVER IN BESAR URBAN VILLAGE, MEDAN LABUHAN DISTRICT IN 2022 - Cici Ramadhani, Aina; Agita Pasaribu, Aggridita; Khairina Ashar, Yulia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Dengue hemorrhagic fever (DHF) is still a public health problem in urban and semi-urban areas. DHF can carry the risk of death, and disturb the public because of its very fast spread. The main cause of DHF is the female mosquito of the Aedes aegypti type. The purpose of this activity is to provide knowledge and understanding of the community about the dengue outbreak in the Besar Urban Village area as well as to provide knowledge and understanding of the community about dengue prevention in the area. the community service method is carried out in several stages of activity. Starting with the Self-Inspection Survey (SMD), distributing the Self-Inspection questionnaire to sub-districts 2, 3, 4, and 5 which was confirmed by the lurah. Next, conduct a village meeting to determine the priority of the problem and the last intervention activity. Based on the results of the analysis, it was shown that there was an increase in the knowledge of residents about Dengue Hemorrhagic Fever (DHF) from before the activity was carried out. Where the increase in knowledge from the pretest and posttest scores affects outreach activities, providing mosquito repellent (Abate & Soffel), and cooperation.